2020
DOI: 10.1186/s12967-020-02267-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the association between tumor glycolysis and immune/inflammation function in breast cancer

Abstract: Background: Metabolic reprogramming, immune evasion and tumor-promoting inflammation are three hallmarks of cancer that provide new perspectives for understanding the biology of cancer. We aimed to figure out the relationship of tumor glycolysis and immune/inflammation function in the context of breast cancer, which is significant for deeper understanding of the biology, treatment and prognosis of breast cancer. Methods: Using mRNA transcriptome data, tumor-infiltrating lymphocytes (TILs) maps based on digitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 64 publications
0
59
0
Order By: Relevance
“…Li et al explored the association between glycolysis and the immune cells. They concluded that most of the immune cell type enrichment scores were remarkably higher in the high glycolysis group, including CD8 + naive T cells, Th1 cells, Th2 cells, NK cells, Monocytes, Macrophages M1, DC, and so on [ 43 ]. Taken together, glycolysis activity was closely related to immune activity, and immune function was activated as glycolysis was elevated in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al explored the association between glycolysis and the immune cells. They concluded that most of the immune cell type enrichment scores were remarkably higher in the high glycolysis group, including CD8 + naive T cells, Th1 cells, Th2 cells, NK cells, Monocytes, Macrophages M1, DC, and so on [ 43 ]. Taken together, glycolysis activity was closely related to immune activity, and immune function was activated as glycolysis was elevated in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cascone et al found that in patients with melanoma and NSCLC, high glycolytic activity will be accompanied by poor immune cell infiltration, such as cytoxic T cells, T helper cells, memory T cells, macrophases, or natural killer (NK) cells reduction [ 46 ]. Li et al found that high glycolysis group had a higher immunescore and higher TIL percentage in breast cancer, however, the immune cells with anti-tumor effect were not enriched, and concluded that high glycolysis was associated with immunosuppression of tumor microenvironment [ 47 ]. In our study, the expression levels of CD8 T cells and resting mast cells were significantly higher in the low-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…Breast IDC is the most common pathological type of breast tumor, and morbidity and mortality from this cancer continue to increase ( Harbeck et al, 2019 ; Badve & Gokmen-Polar, 2019 ). There is evidence that changes in glycolysis-related genes have multiple effects on the prognosis of these patients ( Li et al., 2020a ; Li et al., 2020b ; Chen et al, 2019 ). In particular, tumor cells reprogram the glycolysis pathway to accommodate the increased energy required for malignant transformations, including invasion and metastasis ( Shen et al, 2020 ; Abbaszadeh, Cesmeli & Biray, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of women with breast IDC is related to the activation or silencing of various biological functions in tumor tissues and signaling pathways. There are prognostic models based on tumor immunity and autophagy, but no models have exclusively focused on IDC ( Li et al., 2020a ; Li et al., 2020b ; Zhang, Zhang & Yu, 2019 ; Hu et al, 2020 ) and few models examined genes that function in basic metabolism.…”
Section: Introductionmentioning
confidence: 99%